2012
DOI: 10.1111/j.1502-3885.2011.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary denudation of southern Fennoscandia – evidence from the marine realm

Abstract: Throughout the last 1.1 million years repeated glaciations have modified the southern Fennoscandian landscape and the neighbouring continental shelf into their present form. The glacigenic erosion products derived from the Fennoscandian landmasses were transported to the northern North Sea and the SE Nordic Seas continental margin. The prominent sub‐marine Norwegian Channel trough, along the south coast of Norway, was the main transport route for the erosion products between 1.1 and 0.0 Ma. Most of these erosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…This may have been due to the distribution of cores, where a bias towards coarser grained sediments was incorporated into the selection of sites. However, on non-subsiding continental shelves, interglacials are periods of relative sedimentary quiescence when compared to glacial stages, thus having less persistence in the sedimentary record ( Hjelstuen et al, 2012 ). Further, there is a greater chance of reworking as successive erosion phases modify the morphological and sedimentary evidence of previous periods, and as a consequence the most recent phase of erosion and deposition is best preserved.…”
Section: Discussionmentioning
confidence: 99%
“…This may have been due to the distribution of cores, where a bias towards coarser grained sediments was incorporated into the selection of sites. However, on non-subsiding continental shelves, interglacials are periods of relative sedimentary quiescence when compared to glacial stages, thus having less persistence in the sedimentary record ( Hjelstuen et al, 2012 ). Further, there is a greater chance of reworking as successive erosion phases modify the morphological and sedimentary evidence of previous periods, and as a consequence the most recent phase of erosion and deposition is best preserved.…”
Section: Discussionmentioning
confidence: 99%
“…Sediment transport related to GDFs may have been operating on the North Sea Fan for the last 1.1 Myr, i.e., since the first ice-stream evidence in the Norwegian Channel 33 . The North Sea Fan received terrigenous sediment from hinterland-to-deep-sea sediment-routing systems with a catchment of c. 215,000 km 2 , and comprises a sediment volume of c. 32,000 km 3 34 , 37 . Vertical erosion has been estimated to 164 m based on volume backstripping to the catchment 34 , and has been modelled from 200 to 600 m for the route of the Norwegian Channel Ice Stream 35 .…”
Section: Introductionmentioning
confidence: 99%
“…The North Sea Fan received terrigenous sediment from hinterland-to-deep-sea sediment-routing systems with a catchment of c. 215,000 km 2 , and comprises a sediment volume of c. 32,000 km 3 34 , 37 . Vertical erosion has been estimated to 164 m based on volume backstripping to the catchment 34 , and has been modelled from 200 to 600 m for the route of the Norwegian Channel Ice Stream 35 . With a total annual output of 1.1 Gt of sediment (equivalent to 8000 m 3 /yr per meter width of ice stream front), the Norwegian Channel Ice Stream was an extremely powerful sediment transport agent in the Late Quaternary 36 , 37 .…”
Section: Introductionmentioning
confidence: 99%
“…Nyg ard et al (2005) suggested that the NCIS advanced to the shelf edge during Marine Isotope Stages (MIS) 2, 6, 8, 10 and 12. Furthermore, it has been estimated that close to 50% of the sediments derived from the catchment area of the NCIS through the Quaternary were deposited in the North Sea Fan, located on the continental slope north of the channel (Hjelstuen et al 2012). As such, the Norwegian Channel is the product of multiple glaciations and not merely a Late Weichselian feature.…”
mentioning
confidence: 99%